Analysis of the integration of medical and nursing care and its association with depression and anxiety among medical staff in the Jinhua area - Sheng, An; Yu, TaoTao; Yu, YanLi; Zhang, MengDi; Zeng, Ye; Ye, Ling (Frontiers in Psychiatry, 2025)
ObjectiveTo evaluate the relationship between implementation of the medical–nursing care integration model and the psychological health (depression and anxiety) of medical staff in the Jinhua area.MethodsA total of 1,022 elderly patients and 182 medical staff from four institutions in Jinhua were surveyed. Patient information, service utilization, and medical costs were collected, while staff familiarity with the Patient-Driven Payment Model (PDPM) and their mental health were assessed using the PHQ-9, GAD-7, and SCL-90 scales. Statistical analyses were conducted to explore associations between PDPM familiarity and psychological outcomes.ResultsMost medical staff reported high familiarity with PDPM and successful adaptation to the integrated model. Despite this, nearly 10% of staff experienced symptoms of depression and 8% reported anxiety. Statistical analysis indicated that higher PDPM familiarity was significantly associated with lower rates of depression, anxiety, and overall psychological distress.ConclusionThe integration of medical and nursing care in Jinhua appears to improve not only the efficiency of elderly services but also supports the mental health of medical staff. However, psychological risks remain, highlighting the need for integrated care models to embed ongoing mental health support mechanisms for healthcare professionals.